Physical interpretation of probability density functions of bubble-induced agitation. (9th November 2016) - Risso, Frédéric
Abstract : A stochastic model is presented for the probability density function (p.d.f.) of the liquid velocity fluctuations generated by high-Reynolds-number rising bubbles. It considers three elementary sources of fluctuations: the potential flow disturbance around each bubble; the average bubble wakes, which are assumed to decay exponentially; and the turbulent agitation resulting from the flow instability, which is assumed to be isotropic, homogeneously distributed all over the flow and statistically independent of the two others. The model reproduces well and explains the characteristics of the experimental p.d.f.s: exponential tails, asymmetry of vertical fluctuations and evolution with the gas volume fraction. The model involves two a priori unknown parameters: the volume of the wake and the velocity scale of the turbulent agitation. Because some parts of the probability functions depend only on a single contribution, these two parameters can be uniquely and independently determined from experimental p.d.f.s. This defines an objective method to separate the various kinds of fluctuations and allows one to determine the contribution of each of them to the total agitation.